Shiny bronze in glassy matter: an inconspicuous piece of slag from the Bronze Age mining site of Musiston (Tajikistan) and its significance for the development of tin metallurgy in Central Asia - Berger, Daniel; Brügmann, Gerhard; Friedrich, Ronny; Lutz, Joachim; Meyer, Hans-Peter; Pernicka, Ernst (Archaeological and anthropological sciences, 2022)
This paper aims at contributing to a better understanding of the beginnings of tin and bronze metallurgy in Central Asia by investigating a hitherto unique piece of a bronze slag. The object was originally discovered as a stray find only 4 km away from the large copper-tin deposit of Musiston in Tajikistan. It contains many prills of bronze and copper as well as small charcoal particles. Radiocarbon dating of the charcoal places the slag in a period between 1900 and 1400 BCE and thus in the Late Bronze Age of the region. This date coincides with radiocarbon dates of relics from underground galleries of the Musiston deposit. Chemical and microscopic examination demonstrated the slag to be a relic of a co-smelting process, in which a natural assemblage of tin and copper minerals was smelted simultaneously. Both the chemical and the tin and copper isotope compositions clearly link the slag to the nearby polymetallic ores from Musiston, of which an extensive dataset is presented. The artefact's lead isotope ratios and increased iron concentration in turn indicate intentional fluxing of the original ore charge with iron-dominated ores. These results are the first tangible evidence of a smelting process of tin ores in the entire region and therefore add a new dimension to the findings from previous mining archaeological investigations. At the same time, the results give significant information about the smelting process of secondary polymetallic ores from Musiston and help in assessing the scientific data of Bronze Age bronze artefacts from Central Asia.